PENGARUH KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Pramuswara, Novita Andika; Haerudin, Haerudin (Universitas Bhinneka PGRI, 2024)
The purpose of this research is to assess the extent to which students' understanding of mathematical concepts influences their ability to solve mathematical problems. This study was conducted at one of the junior high schools (SMPN) in Karawang Regency, using a quantitative approach and non-experimental method. The research subjects involved 34 students from class VII A, selected using purposive sampling technique. Data collection was carried out through two test instruments consisting of a set of descriptive questions covering indicators of both mathematical conceptual understanding and mathematical problem-solving skills. Simple linear regression analysis was employed in data processing for this research. The results obtained indicate, at a 95% confidence level, a significant influence of mathematical conceptual understanding on mathematical problem-solving abilities.